2010
DOI: 10.1111/j.1365-2664.2009.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability and the persistence of seed‐eating bird populations in agricultural landscapes : a mechanistic modelling approach

Abstract: Summary 1.Reductions in resource availability, associated with land-use change and agricultural intensification in the UK and Europe, have been linked with the widespread decline of many farmland bird species over recent decades. However, the underlying ecological processes which link resource availability and population trends are poorly understood. 2. We construct a spatial depletion model to investigate the relationship between the population persistence of granivorous birds within the agricultural landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…forestry intensification) typically change interior forest structures over long periods of time. As a consequence, species vanish, immigrate or change in abundance as a response to such alterations (Bradbury et al, 2005;Butler et al, 2010;Renner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…forestry intensification) typically change interior forest structures over long periods of time. As a consequence, species vanish, immigrate or change in abundance as a response to such alterations (Bradbury et al, 2005;Butler et al, 2010;Renner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach to ecological studies is strongly advocated nowadays (cf. Sekercioglu 2006;Wenny et al 2011), especially in the context of the observed dramatic declines in seed-eating bird populations because of agricultural intensification (Panek 2005;Butler et al 2010;PECMBS 2011), and the resulting overall decline of ecological services provided by birds (Sekercioglu 2006;Wenny et al 2011). In this work we analyse the structure of the seed pool present in faecal samples of these three granivores; special attention is paid to the habitat used as the feeding site and the features of seeds that enhance the probability of surviving ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the current version of the model is simplified by the assumption of a fixed territory size. Territory size is often variable and adapted to food supply, so is has to be tested to what extent such modifications would alter the results (Butler et al ., ). Though, we have shown that in the case of Skylark ( A. arvensis ), there is a good correspondence between simulated and measured average abundance, despite the simplicity of the model (see Fig.…”
Section: Discussionmentioning
confidence: 97%